Combined Sonographic Testing Index and Prediction of Adverse Outcome in Preterm Fetal Growth Restriction - Odibo, Anthony O.; Goetzinger, Katherine R.; Cahill, Alison G.; Odibo, Linda; Macones, George A. (American Journal of Perinatology, 2014)
Objective We sought to test the hypothesis that a combined sonographic scoring system (CSTI) that incorporates features of the biophysical profile (BPP) and multivessel Doppler evaluation improves prediction of adverse outcomes in preterm intrauterine growth restriction.Methods This was a prospective cohort study of growth-restricted fetuses with abnormal umbilical artery (UA) Doppler studies, defined as pulsatility index (PI) > 95th percentile for gestational age or absent/reversed end diastolic flow. Fetuses were followed with weekly BPP and Doppler evaluation of the UA, middle cerebral artery (MCA), and ductus venosus (DV) until the time of delivery. The cerebroplacental Doppler ratio (CPR) was then calculated (MCA PI/UA PI). MCA PI < 5th percentile, MCA peak systolic velocity (PSV) > 1.5 multiples of the median, DV PI > 95th percentile with or without absent/reversed flow, and CPR < 1.08 were considered abnormal. Using logistic regression modeling, a weighted scoring index for the prediction of a composite fetal vulnerability index (FVI), which included 5-minute Apgar score < 3, cord pH < 7.2, seizures, necrotizing enterocolitis, grade 4 intraventricular hemorrhage, periventricular leukomalacia, and neonatal death, was developed. A receiver operating characteristic (ROC) curve was used to identify the best score associated with the FVI.Results Of 66 patients meeting inclusion criteria over a 5-year period, 17 (25.8%) had a positive FVI. Abnormal BPP (< 8), MCA PI, MCA PSV, DV PI, and CPR were observed in 6, 27.3, 13.6, 56.1, and 33.3% of patients, respectively. From the logistic regression model, a CSTI was developed including a score of 1 for abnormal BPP, 3 for MCA PSV, 1 for DV, 6 for CPR, and 3 for oligohydramnios. The ROC curve identified a score of ≥ 7 to be the best predictor of FVI with sensitivity of 35.1% and specificity of 91.8% and a positive likelihood ratio of 4.3 (area under ROC curve 0.73). These test characteristics were better than those for any of the individual component antenatal tests.Conclusion Although this novel scoring system performs modestly in predicting adverse outcomes in FGR, it appears to perform better than any individual antenatal test currently available.
Keywords: preterm fetal growth restriction; Doppler evaluation; biophysical profile; adverse pregnancy outcomes